Is Parental Longevity Associated With the Cardiovascular Risk and the Successful Aging of Their Offspring? Results From the Multinational MEDIS Study. (February 2017) - Tyrovolas, Stefanos; Polychronopoulos, Evangelos; Mariolis, Anargiros; Piscopo, Suzanne; Valacchi, Giuseppe; Makri, Kornilia; Zeimbekis, Akis; Tyrovola, Dimitra; Bountziouka, Vassiliki; Gotsis, Efthimios; Metallinos, George; Tur, Josep-Antoni; et al.
The aim of the present study was to evaluate the role of parental longevity and parental cardiovascular disease (CVD) history in CVD risk and successful aging of a random sample of older adults living in the Mediterranean basin and who participated in the MEDiterranean Islands (MEDIS) study. During 2005 to 2011, 2663 elders were voluntarily enrolled. A multidimensional successful aging index consisting of 10 components was used. Paternal and maternal longevity was defined as those older participants of whom both parents lived above the age of 90. The burden of CVD-related factors (CVD-RFs) was calculated as the total score of 4 major CVD-RFs (range 0-4). After adjustment, parental longevity was inversely associated with the burden of CVD-RFs ( P = .04). Moreover, parental longevity was positively associated with the older adults' successful aging score (β-coefficient [95% confidence interval]: .38 [0.06-0.71]). Parent's long living was revealed as an important factor for successful aging and for reduced CVD risk, suggesting that further research is needed in the genetic predisposition of longevity.